Mechanistic studies of the adhesion-GPCR latrophilin and its interactions in neural guidance - Jackson, V (2017)
The adhesion GPCRs are a poorly understood and evolutionarily ancient family of cell surface receptors, several of which have emerging functions in the development of the nervous system. aGPCRs comprise a large extracellular domain, providing binding sites for a variety of ligands, alongside a seven transmembrane domain characteristic of GPCRs. It has been proposed that aGPCRs may function as "context-recognisers", using their large ectodomains to bind different combinations of ligands depending on the molecular make- up of the environment. However there is a lack of direct evidence for this at a molecular level. The ectodomain of one subfamily of aGPCRs, the Latrophilins (Lphns) has been shown to directly interact with several ligands with roles in synaptogenesis and neural guidance. The best-validated of these interactions are those with Fibronectin Leucine- Rich Transmembrane (FLRT) proteins and the Teneurins. In addition, FLRT proteins, also interact with Uncoordinated5 (Unc5) proteins, mediating cell repulsion. Here I reveal that the FLRT-binding site of Lphn is bifunctional, mediating both cell adhesion and repulsion, and that Unc5 is capable of influencing the functional outcome of this interaction. Biophysics and structural studies show that fragments of the Lphn, FLRT and Unc5 ectodomains interact in an unusual and homologue-dependent stoichiometry. Despite the fact that Teneurin interacts with Lphn at a distinct site, Teneurin seems incapable of interacting with the Lphn-FLRT-Unc5 complex, but can form a ternary complex with Lphn and FLRT in the absence of Unc5. Alongside this I present a crystal structure of a large portion of a Teneurin ectodomain, revealing the ancient evolutionary origins of this receptor. Together these data provide strong molecular evidence for a role of Lphns as context-recognisers, by their abilities to bind diverse ligands in distinct combinations and variable stoichiometries.